Statutory regulation and industrial conflict in Jamaica. - COWELL, Noel M. (1996)
Discusses the impact of the 1975 Labour Relations and Industrial Disputes Act (LRIDA). Argues that the Act heralded the dominance of the law and the legal profession over industrial relations, and robbed workers of the 'right to strike', which they were presumed to have by virtue of custom and practice. Further, it ushered in a new framework of industrial relations in which the most vulnerable workers are exposed to dismissal for withdrawing their labour.